Liver malfunction of wistar rats induced by combination of benzoic and citric acids as food additive - Abdelgadir, Muawia; Hassan, Mamood; Idris, Salah; Sabahelkhier, Murwan; Ali, Zeineb; Adris, Mohamed; Idris, Omer (International Journal of Medicine, 2017)
This study was aimed to investigate liver function of Wistar rats influenced by oral ingestion of different doses of combination of benzoic and citric acids as food additives. Administered doses were (100, 500 and 1250 mg/kg b.w). Rats' serum GGT and ALP were used as an indicators. Forty four Wistar rats were divided into four groups’ eleven rats in each group, six males and five females. One group was put as control, and the remainder of the three groups received different doses of combination of benzoic and citric acids. Housing in Meck Ni-mir research center Khartoum. They were recived free tab water and prepared food systems liberally. Serum was taken from each rats and analyzed by spectrophotometer. Transverse sections of liver organs were used to prepare Histopathiological slides. A significant (p ≤ 0.05) gradual increase according to increased treatment doses in serum GGT and alkaline phosphatase were observed in treated animals, compared with control. Also there were different signs of liver histopathological changes including plate hyperaemia, hemorhage, haemosidero-sis,diffuse coagulative necrosis ,cytoplasmic vacuolation and sinusoidal dilatation. Change in nuclei. Compared to control all tested animals showed significant (p ≤ 0.05) inccreased body weight. All animals survived till the end of the experiment. We concluded that oral ingestion of combination of benzoic and citric acid causes liver malfunction, so it is preferred to ingest foods and beverages containing combination of benzoic and citric acid with caution. This study was aimed to investigate rats’ liver malfunction induced by oral ingestion of combination of benzoic with citric acid in ratio (1:1/ v: v).